Answer:
x=−3x−7whatish(−4)
Step 1: Flip the equation.
28ah2istw−3x=x
Step 2: Add 3x to both sides.
28ah2istw−3x+3x=x+3x
28ah2istw=4x
Step 3: Divide both sides by 28h^2istw.
28ah2istw
28h2istw
=
4x
28h2istw
a=
x
7h2istw
Answer:
a=x7h2istw
Answer:
435 ft
Step-by-step explanation:
Reference angle = <P = 49° (angle of elevation)
Opposite side = 500 ft
Adjacent side = d = ?
Apply trigonometric function, TOA.
This:
Tan P = opp/adj
Tan 49 = 500/d
d × Tan 49 = 500
d = 500/Tan 49
d = 434.643369 ≈ 435 ft (to the nearest foot)
Answer:
1/4
Step-by-step explanation:
It's 248.3333 (but with the 3s repeating)
We are supposed to explain why the given function can be expressed in form , when .
Since the given function is an exponential function we can express it as .
Now let us substitute x=0 in the given function,
Let us substitute x=0 in our function.
Upon substituting a=1 in our function we will get,
Therefore, our function f can be represented by the formula of the form .